El peritoneo : descripción de un nuevo síndrome, falla peritoneal - Riveros Dueñas, Rafael; Isaza Restrepo, Andrés; Sefair Cristancho, Carlos (Bogotá : Universidad del Rosario, 2014)
....
.....
incluye bibliografía
Keywords: ANATOMÍA HUMANA; PERITONEO